EXTRA VIRGIN OLIVE OIL EFFECT IN THE COMBINATION OF ALCOHOL AND BENZENE ON THE KIDNEY OF RATTUS NOVERGICUS - OPEYEMI ADEBOLA, ADETUNJI; ADEGOKE, ADETUNJI OLUWASEYI; CHIGBOGU, NWOBI JOSEPH; TOYIN, ADETUNJI IYABODE; TOSIN, OGUNBIYI BABAFEMI; LINDA, NWOBI NNENNA (Innovare Journal of Medical Sciences, 2021)
Objective: This study investigated the use of extra virgin olive oil (EVOO), which is said to possess anti-inflammatory components as an ameliorative substance for the induced inflammation. Methods: Forty-eight female Wistar rats were used for this study. They were divided into eight (1–8) groups (n=6); Control, Ethanol, Benzene, E+B, E+O, B+O, E+B+O with the administration of 25% Ethanol, 200 mg/kg/b.w Benzene, 2 ml (O) EVOO in respect to the tagged grouping names. Animals were euthanized through cervical dislocation after the last day of administration and the liver was excised and part was fixed in formalin solution of 10% for histological processing and the other part was homogenized for biochemical assay in phosphate buffer before centrifugation. Results: Histological evidence creates an understanding of the nephrons in which benzene and ethanol manifest likewise the mitigated ability of EVOO. The relative organ weight provides information on the extent of the damage on nephrons. The kidney test level is significantly expressed. Conclusion: Ethanol and benzene in combination cause serious damage; also, they separately induce nephrons dysfunction. EVOO was shown to mitigate these nephrons damages.